Regulation and pricing of pharmaceuticals: reference pricing or price cap regulation? - Kurt R. Brekke; Astrid L. Grasdal; Tor Helge Holmås (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the relationship between regulatory regimes and pharmaceutical firms' pricing strategies using a unique policy experiment from Norway, which in 2003 introduced a reference price (RP) system called index pricing for a sub-sample of off-patent pharmaceuticals, replacing the existing price cap (PC) regulation. We estimate the effect of the reform using a product level panel dataset, covering the drugs exposed to RP and a large number of drugs still under PC regulation in the time before and after the policy change. Our results show that RP significantly reduces both brand-name and generic prices within the reference group, with the effect being stronger for brand-names. We also identify a negative cross-price effect on therapeutic substitutes not included in the RP-system. In terms of policy implications, the results suggest that RP is more effective than PC regulation in lowering drug prices, while the cross-price effect raises a concern about patent protection.
Keywords: I11; L13; L51; L65; 330; Pharmazeutisches Produkt; Arzneimittelmarkt; Preiswettbewerb; Anreizregulierung; Norwegen